The dust-jacket considered - Margit J Smith (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This article addresses the  history of protective book coverings from earliest times to their current use;  their design as it mirrors changes in the graphic arts and materials over the past century; scholarly, commercial, and marketing use of dust-jackets, collections in institutions. Treatment in library settings and availability to students and users will also be discussed. Findings, suggestions and instructions for their preservation,  pros and cons of retention, importance in the rare book trade, and the production of fake and facsimile dust-jackets are also considered.